2021
DOI: 10.2196/preprints.33336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

User experience and user acceptance of a speech recognition-based diagnostic management application: mobile health at point-of-care (Preprint)

Abstract: BACKGROUND In-patient management like ordering medical tests is time-consuming and burdens physicians on the ward with non-clinical tasks. We developed and implemented a smartphone-based mobile application (MA) that uses speech recognition for the ordering of radiological examinations. While we could show that the MA supported process was faster, its acceptance and usability remaines unknown. OBJECTIVE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The studies presented evidence on user experiences of m-linked POC diagnostics. The included articles comprised two cross-sectional studies [24,25], two qualitative studies [26,27], a cohort study [28], three surveys [29][30][31], and one mixed method study [32].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies presented evidence on user experiences of m-linked POC diagnostics. The included articles comprised two cross-sectional studies [24,25], two qualitative studies [26,27], a cohort study [28], three surveys [29][30][31], and one mixed method study [32].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…190 The included studies were conducted in various countries (Fig 2). Three studies were conducted in the United States of America (USA) [25,27,31], one in Ghana [26], one in South Africa [24], one in the United Kingdom (UK) [29], one in Australia [32], and one in Germany [30]. A cohort study by Jacobson et al (2020) also reported findings from the USA, Australia, Germany, Italy, Spain, Ireland, Brazil, Portugal, India, and Argentina [28].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations